quadratic equation.

Asked by khushal305 | 9th Sep, 2009, 08:41: PM

Expert Answer:

abx2 = (a+b)2(x-1)

A = (a+b)2

abx2 = A(x-1)

abx2 - Ax + A = 0

x = [A ± (A2 - 4abA)]/2ab

{ A2 - 4abA = A(A - 4ab) = (a+b)2((a+b)2 - 4ab) = (a+b)2(a2 + 2ab + b2 - 4ab) = (a+b)2(a-b)2 }

x = [A ± (A2 - 4abA)]/2ab

x =  [(a+b)2 ±  (a+b)(a-b)]/2ab

x = (a+b) [a+b ± (a-b)]/2ab

x = {(a+b)/b, (a+b)/a}

Regards,

Team,

TopperLearning.

Answered by  | 9th Sep, 2009, 10:31: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.